The Role of Whatsapp Business Application in Improving the Service Performance of Front Office Staff of Four Points By Sheraton Hotel Batam - Junita, Junita; Sukmamedian, Haufi; Lubis, Arina Luthfini; Supardi, Supardi (Jurnal Manajemen Pelayanan Hotel, 2024)
Effective communication is crucial in the hospitality industry, yet there remain gaps in understanding how digital tools influence service quality and guest satisfaction. This study investigates the impact of WhatsApp Business on communication practices and service delivery at Four Points by Sheraton Batam. With the rapid evolution of technology, the hospitality sector must adapt to meet contemporary guest expectations. Utilizing a qualitative research approach, data were gathered through in-depth interviews and observations of staff and guest interactions over a three-month period. Findings reveal that WhatsApp Business significantly enhances responsiveness, streamlining communication between staff and guests. Staff reported that the application facilitated quicker resolutions of guest requests and complaints, ultimately contributing to a more positive overall experience. Moreover, the study found that effective use of WhatsApp Business improved accessibility, making it easier for guests to voice their needs. While these results are promising, the research also highlights that factors such as staff training, management commitment to customer service, and existing operational protocols play critical roles in determining overall service quality. This study underscores the relevance of integrating digital communication tools within the hospitality sector and provides insights applicable to other service-oriented fields, including school counseling. In conclusion, the adoption of digital tools like WhatsApp Business can substantially elevate guest experiences, aligning with contemporary expectations in the digital age. However, limitations such as a small sample size and the focus on a single hotel indicate the need for further research to explore the long-term effects of digital communication tools in enhancing service quality within the hospitality industry.